The integration of gamification in educational robotics as a tool to enhance discovery learning: teachers’ perceptions - Maria Chatzikyrkou; Apostolos Tsagaris (Institute of Advanced Engineering and Science, 2026)
The study examines the combined use of gamification and educational robotics as a means of enhancing the learning experience and fostering active student engagement. Through a literature review, the benefits of this approach are presented, including increased motivation, the development of creativity, the cultivation of collaboration, and problem-solving skills. A new educational methodology is proposed, based on the analysis, design, development, implementation, evaluation (ADDIE) model in combination with gamification techniques. The approach aims to create a more engaging, effective, and interactive learning environment. This methodology was evaluated through a usability study involving 302 educators from primary, secondary, and tertiary education institutions across Greece. Data were collected via an adapted software usability measurement inventory (SUMI) questionnaire and analyzed using non-parametric statistical tests including Mann-Whitney U and Kruskal-Wallis tests. The results indicate that participants generally evaluated the methodology favorably across all measured dimensions. The strongest influences on these perceptions derived from personal background variables such as age, educational level, and professional training. Specifically, perceptions related to learning and access to technology were more sensitive to these factors. Correlation analysis further confirms that concepts such as effectiveness, usefulness, and satisfaction are interconnected, reinforcing the notion that improving one aspect of the experience (e.g., training or support) can positively impact others. The analysis is comprehensive, appropriately executed, and provides actionable insights for tailoring future implementations of the methodology based on educators’ demographic characteristics and training levels. The study concludes that the integrated gamification-robotics methodology demonstrates strong potential for implementation across diverse educational contexts, with professional development and information and communication technologies training identified as critical success factors.